2023
DOI: 10.1093/crocol/otad027
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Intestinal Ultrasound in Clinical Decision-Making for Inflammatory Bowel Disease

Abstract: Background There is a clinical need to improve monitoring of inflammatory bowel disease (IBD) disease activity. Despite being used regularly in European countries, intestinal ultrasound (IUS) has been implemented less in the United States for unclear reasons. Aims The aim of this study is to illustrate how IUS can be used as a clinical decision-making tool in an American IBD cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In UC, as opposed to CD, the clinical scores significantly correlate with disease activity as determined by IUS [6,94].…”
Section: Disease Activity Evaluationmentioning
confidence: 92%
See 1 more Smart Citation
“…In UC, as opposed to CD, the clinical scores significantly correlate with disease activity as determined by IUS [6,94].…”
Section: Disease Activity Evaluationmentioning
confidence: 92%
“…Non-invasive procedures include clinical parameters (different for CD and UC), blood (erythrocyte sedimentation rate-ESR; C-reactive protein-CRP), and stool (faecal calprotectin-FC) examinations. A plethora of biomarkers (such as genetic, metabolic, and bacterial flora) have been intensely studied, but they have yet to be put into use due to their contradictory results [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, IUS is noninvasive and evaluates the morphology of all layers of the intestinal wall while providing insight into mural stratification, bowel wall thickness, mesenteric fat, lymph nodes, and blood flow as assessed by doppler. 2 In stricturing disease, dilation of the proximal lumen can be seen in addition to conglomeration of loops, adjacent fistulas, and abscesses. Additional modalities, such as doppler ultrasound or contrast-enhanced ultrasound, can be used to examine intramural blood flow and differentiate between active inflammation and fibrotic mucosa.…”
Section: Evidence Supporting Iusmentioning
confidence: 99%
“…Additionally, IUS can be used for long-term disease activity monitoring, especially due to the lack of correlation between symptoms and noninvasive objective markers of disease activity, allowing for prompt and early change in IBD treatment. 2 In what follows, we briefly summarize the evidence for IUS’s utility and provide a practical framework for implementing IUS in clinical practice in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, its diagnostic accuracy approaches that of more elaborate conventional radiological examinations like MRE. 17,18 It is worth noting that other studies have already demonstrated the efficacy of clinical decision-making involving IUS findings in reducing inflammation in patients with IBD, 19 and IUS is increasingly finding application in CD management, [20][21][22] underscoring its potential utility as a pivotal tool in striving for transmural remission. Inflammatory bowel disease gastroenterologists should be encouraged to consider transmural remission as a viable treatment goal for CD management.…”
mentioning
confidence: 99%